Mekanisme Kerja & Penggunaan Klinis N-Acetylcystein (NAC) Pada Penyakit Paru & Saluran Napas - Poty, Pitha Maykania; Mustofa, Syazili; Kurniawaty, Evi; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Lung disease is one of the leading causes of illness and death worldwide. Lung disease can be caused by inflammation of the tissues due to oxidative stress. Oxidative stress plays a role in the pathogenesis of lung disease, both acute and chronic. Oxidative stress in the lungs occurs when antioxidant capacity is depleted due to external exposures, such as changes in oxygen pressure due to pollutants, and internal exposures, such as systemic disease and activation of inflammatory cells in response to exposure. Oxidative stress is an imbalance in the production of oxidants and antioxidants in the body's metabolism. In lung disease, oxidative stress increases in endogenous metabolism so exogenous antioxidants in the form of N-acetylcysteine ​​(NAC) are needed. NAC is a glutathione precursor that can replenish total thiols (cysteine, cysteinylglycine, glutathione, and homocysteine). The mechanism of action of NAC is by interacting with ROS so that it can increase antioxidant capacity again. Oxidative stress can deplete antioxidants, NAC will release Thiol groups directly thereby neutralizing oxidants such as N and NO2. Clinically, NAC has been proven to be useful as a treatment for lung diseases such as COVID-19, asthma, bronchiectasis, COPD, and TB at high doses, namely 1200 mg/day.